Romantic Organ Sonata: The Main Stages - Tamilla Sarimsakova Alimovna (Scientific Trends, 2025)
This scholarly article examines the evolution of the organ sonata genre, tracing its trajectory from the late 17th century to its establishment as a distinct musical form in the 19th century. The study delineates the key stages in the development of the organ sonata, starting with Baroque prototypes and culminating in its zenith during the Romantic era's second half.
Keywords: Organ sonata, genre, romanticism, baroque era, cycle, Bach, Mendelssohn.